Pustular psoriasis: pathophysiology and current treatment perspectives - Benjegerdes KE (Dove Medical Press, 2016)
Katie E Benjegerdes,1 Kimberly Hyde,2 Dario Kivelevitch,3 Bobbak Mansouri1,4 1Texas A&M Health Science Center College of Medicine, Temple, 2Texas A&M Health Science Center College of Medicine, Round Rock, 3Division of Dermatology, Baylor University Medical Center, Dallas, 4Department of Dermatology, Scott and White Hospital, Texas A&M Health Science Center College of Medicine, Temple, TX, USA Abstract: Psoriasis vulgaris is a chronic inflammatory disease that classically affects skin and joints and is associated with numerous comorbidities. There are several clinical subtypes of psoriasis including the uncommon pustular variants, which are subdivided into generalized and localized forms. Generalized forms of pustular psoriasis include acute generalized pustular psoriasis, pustular psoriasis of pregnancy, and infantile and juvenile pustular psoriasis. Localized forms include acrodermatitis continua of Hallopeau and palmoplantar pustular psoriasis. These subtypes vary in their presentations, but all have similar histopathologic characteristics. The immunopathogenesis of each entity remains to be fully elucidated and some debate exists as to whether these inflammatory pustular dermatoses should be classified as entities distinct from psoriasis vulgaris. Due to the rarity of these conditions and the questionable link to the common, plaque-type psoriasis, numerous therapies have shown variable results and most entities remain difficult to treat. With increasing knowledge of the pathogenesis of these variants of pustular psoriasis, the development and use of biologic and other immunomodulatory therapies holds promise for the future of successfully treating pustular variants of psoriasis. Keywords: psoriasis, pustular psoriasis, generalized pustular psoriasis, von Zumbusch, impetigo herpetiformis, acrodermatitis continua of Hallopeau, palmoplantar pustulosis, biologic